GAMBARAN POLA MAKAN PENDERITA DIABETES MELITUS RAWAT JALAN DI PUSKESMAS KOTANOPAN KABUPATEN MANDAILING NATAL TAHUN 2013 - Marlina Nasution; Jumirah .; Muhammad Arifin Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
The technological development make a change of public behavior and life style like food pattern unsuited with the body necessity and less activity until having an effect on improve the diabetes mellitus case. The objective of this research to know the food pattern of diabetes mellitus at Puskesmas Kotanopan Kabupaten Mandailing Natal. This study adopted descriptive survey with design method in cross sectional. The sample on the research known in total sampling involved 60 patients with diabetes mellitus as out-patient. The data used such as primary and secondary data. Primary data was taken by interview with questionnaire, in food recall and food frequency forms. Secondary data was taken from Puskesmas, such as general description and data of patient with diabetes mellitus. In research the characteristics of patient mostly aged 50-64 years old, female. In taken carbohydrate, protein and fat is certainty exceeding standard rate namely as recommended carbohydrate 48.4 %, protein 40,0 % and fat 61,7 % respectively. The meal time of those patient diabetes mellitus should more than 3 hours. Recommended to health care improve of service the information to patient with diabetes mellitus so as to more discipline admission of food pattern, and to the patient with diabetes mellitus so as comply food pattern as requested, so that they can develop good habits and focused on the health living. Keywords : type, total and meal hour, diabetes mellitus